Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/elan.200603556
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Oxidation at Per(6‐deoxy‐6‐thio)‐α‐Cyclodextrin Monolayer Modified Gold Electrodes

Abstract: The gold electrode is functionalized by sequential self-assembly of a monolayer of the title thiolated cyclodextrin with and without dopamine included in the cavities. The structure of a-cyclodextrin modified gold electrode is carefully characterized using STM and AFM. Surface complexation of dopamine is examined and its association constant is evaluated. Chemical reactions accompanying the electrode process of dopamine, which interfere in the electrochemical dopamine determination, are described and the condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…This can be attributed to the redox reactions of the leucodopaminechrome/ dopaminochrome couple, Eq. (5), which is formed through the cyclization reaction of dopamine-quinone [30,31]. However, this reduction peak is absent in the presence of the sulfonated b-CD, which indicates that the cyclization reaction of the quinone, generated through the oxidation of DA, is inhibited when the DA is included in the cyclodextrin cavity.…”
Section: Influence Of Ph Cations and Anions On Formation Of The Inclmentioning
confidence: 99%
“…This can be attributed to the redox reactions of the leucodopaminechrome/ dopaminochrome couple, Eq. (5), which is formed through the cyclization reaction of dopamine-quinone [30,31]. However, this reduction peak is absent in the presence of the sulfonated b-CD, which indicates that the cyclization reaction of the quinone, generated through the oxidation of DA, is inhibited when the DA is included in the cyclodextrin cavity.…”
Section: Influence Of Ph Cations and Anions On Formation Of The Inclmentioning
confidence: 99%
“…This reaction leads to the regeneration of dopamine making it available for further electrochemical oxidation, complicating the analysis [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…pH was evaluated to be 49mV/pH unit, which was very close to the anticipated Nernstian value for a two-electron, two-proton process [40]. A linear regression analysis Epa =0.447-0.049 pH (correlation coefficient, R 2 = 0.987) showed that the uptake of electrons was accompanied by an equal number of protons.…”
Section: Effect Of Phmentioning
confidence: 54%